PENGARUH PEMBELAJARAN TEMATIK-INTEGRATIF BERBASIS SOSIOKULTURAL TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS III SEKOLAH DASAR - Arifin, Slamet (Universitas Muhammadiyah Surakarta, 2016)
This study aims to determine the effectiveness of the application of thematic learning modelbased integrative sosiokultural for students of class III Elementary School in Purbalingga.The research design was quasi experimental with one group pre-test and post-test design. The subject of research involved are students of class III SD N Pengadegan Pengadegan 1 and 2 a total of 56 students, where each class consists of 28 students. In this research, students of class III SD N Pengadegan 1 is determined as the control class (with thematic learning-integrative usual) and the third grade students of SD N Pengadegan 2 as the experimental class (using the model of thematic learning-integrative-based sociocultural. The results showed that there were differences the final results were significant between control classes using model-integrative thematic regular and classroom experiment that uses thematic learning model-based integrative socio-cultural. it is obtained from the t-test with p 0.05 then there is also a significant difference,namely with sig = 0.0006.